Legal Analysis of Refugee Protection in Non-Signatory States to the 1951 Convention: A Case Study of Refugees in the North Sumatra - Amalia Wiliani; Aidul Fitriciada Azhari (Jurnal Hukum Sasana, 2026)
This study examines refugee protection in Indonesia, a country that has not ratified the 1951 Convention Relating to the Status of Refugees and its 1967 Protocol. The research focuses on the legal mechanisms applied in the jurisdiction of the North Sumatra Regional Office of the Ministry of Immigration and Corrections. It aims to explore (a) how international instruments govern refugee protection, (b) how Indonesia’s domestic legal framework functions despite non-ratification, and (c) what strategic measures are required to strengthen national and regional protection systems.Using both normative and empirical legal methods, the study analyzes relevant statutes, international conventions, and interviews with government officers. The findings reveal that, although Indonesia is not formally bound by the 1951 Convention, the moral and constitutional principles of refugee protection apply through its human-rights commitments. Presidential Regulation No. 125 of 2016 on the Handling of Refugees from Abroad provides administrative recognition but lacks comprehensive legal certainty and long-term solutions such as integration, education, and employment access. Strengthening domestic legislation, empowering local governments, and promoting inter-sectoral collaboration are essential for ensuring humane and sustainable refugee protection in Indonesia